Travessias de uma experiência creep no ensino superior: verdades, relações e subjetividades - Mujica, Juan Bolivar dos Santos Peña (My University, 2020)
This paper aims at analyzing the discourses made by undergraduate students with physical disabilities. This analysis will be conducted with Michael Foucault´s archeogenealogy. In this regard, the research goes through the many different historical perspectives about the abnormal subject in order to showcase the transformations and ruptures which took place within both the regimen of truth and the constitution of knowledge regarding abnormality throughout time. Semi structured interviews were performed with three students, with special focus to their experiences in the academic environment, exploring the challenges they lived, their relationships with professors and peers as well as their life trajectories. In a first moment of the analysis called historical perspective, a theory was created regarding the origin of the court jester during the Medieval Age and how anomalies were used for theatrical ends, transforming them in the beginning of capitalism into a variation of theater called freak shows. In the second half of the 20th Century, a process of medicalization and pathologizing of their condition befell the abnormal. The handicap models which came about afterwards allowed for the subjects to have access to rights and the possibility of inclusion into spaces which were otherwise denied to them. The second moment of analysis, called enunciative spiral, aims at analyzing the emergence of inclusive discourses at the present time, as well as the games of truths and materiality of such enunciations. In a horizon of neoliberal governmentality there is an impetus for inclusion. We live in a performance-based society, in which time is sped up. The massproducing of life, which makes men more and more business owners of themselves, gives way to the contemporary aberration known as the creep. He is immersed in the discourse of optimization of the being, being included in some spaces and excluded from others. In the third moment, called intentionality, it is possible to realize how the relations of power act over these people within an agonistic arena. At the same token in which the power relations aim at normalizing the creep via the impetus of inclusion to better control and govern them, there is freedom to rise against that which wants to subjugate us. Therefore, in the last moment of analysis, entitled statute of presence, there are insights based on the possibility of transgressing, transforming and creating other ways of existing. Therefore, the creep experience in higher education can aid in implementing the current inclusive processes, how we posture ourselves before existence, potentializing our creation bias in face of the instrumentalization and massproduction imposed onto us by the neoliberal governanmentality.
A presente dissertação tem por objetivo analisar os discursos de estudantes com deficiência física no ensino superior, utilizando-se dos aportes arqueogeneálogicos elaborados por Michel Foucault. Nesse sentido, esta pesquisa percorrera as diferentes perspectivas históricas acerca do sujeito anormal, a fim de evidenciar as transformações e rupturas ocorridas nos regimes de verdade, nas constituições dos saberes acerca da anormalidade ao longo do tempo. Realizouse entrevistas semiestruturadas com três estudantes com foco em suas vivencias no ambiente acadêmico, explorando os desafios encontrados, a relação com professores e colegas e suas trajetórias de vida. Em um primeiro momento da análise, denominado perspectiva histórica, teorizou-se sobre o surgimento na Idade Média da figura dos bufões e a utilização das anomalias para fins de teatralização, transformando-se no início do capitalismo em um modo de espetacularização denominado freak shows. Na segunda metade do século XX incidiu sobre o anormal um processo de medicalização e patologização de sua condição. Os modelos de deficiência surgidos posteriormente permitiram a estes sujeitos acessar direitos e a possibilidade de serem incluídos em espaços que outrora foram-lhes negados. O segundo momento da análise, chamado caracol enunciativo, visou analisar a emergência dos discursos inclusivos na atualidade, os jogos de verdades e a materialidade destes enunciados. Em um horizonte de governamentalidade neoliberal há um imperativo por inclusão. Vive-se em uma sociedade do desempenho, onde o tempo é acelerado. A mercantilização do viver que torna o homem cada vez mais empresário de si mesmo dá lugar ao creep, esta aberração contemporânea. Este se situa imerso nos discursos de otimização do ser, estando ao mesmo tempo incluído em determinados espaços e excluído de outros, gradientes de in/exclusão. No terceiro momento chamado intencionalidade, verificou-se como as relações de poder atuam sobre estes sujeitos dentro de uma arena agonística. Da mesma forma que as relações de poder objetivam normalizar o creep por meio do imperativo de inclusão, para melhor controlá-lo e governá-lo, existe a liberdade de insurgir-se perante aquilo que intenta os assujeitar. Assim, o último momento de análise, intitulado estatuto de presença, baseia suas reflexões nesta possibilidade de transgressão, de transformação e de criação de outros modos de existência. Portanto, a experiência creep no ensino superior pode auxiliar na problematização de como está acontecendo os processos inclusivos hoje em voga, a maneira de se conduzir diante da existência, potencializando o viés de criação frente à toda forma de instrumentalização e de mercantilização impostas pela governamentalidade neoliberal
Keywords: Ensino superior; Deficiência física; Subjetividade; Foucault, Michel, 1926-1984; College teaching; Disabilities; Subjectivity